1997
DOI: 10.1038/bjc.1997.55
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial mechanism for the potentiation of cisplatin (CDDP) cytotoxicity by all-trans retinoic acid (ATRA) in human ovarian carcinoma cell lines

Abstract: All-trans retinoic acid (ATRA) has been previously shown to inhibit the proliferation of some human ovarian carcinoma cell lines, and this inhibition was accompanied by cellular changes that were indicative of differentiation (Caliaro et al, 1994). In this work, a pretreatment of these adenocarcinoma cells with ATRA, for their respective doubling time, enhanced cisplatin (CDDP) cytotoxicity in the cell ines that were sensitive to its antiproliferative effect, but not in the ATRA-resistant ones. Results were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…both retinoids differed in their potency to modulate CDDP sensitivity, indicating that additional mechanisms might be responsible for the potentiating effect of ATRA. This is supported by work from Caliaro et al (1997), who suggest that retinoid-mediated alteration of the glutathione-S-transferase activity accompanied by changes in platinum-DNA adduct formation and in epidermal growth factor receptor expression could account for the potentiation of CDDP cytotoxicity in ovarian cancer cells. Retinoids not only represent promising drugs for single-agent anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 74%
“…both retinoids differed in their potency to modulate CDDP sensitivity, indicating that additional mechanisms might be responsible for the potentiating effect of ATRA. This is supported by work from Caliaro et al (1997), who suggest that retinoid-mediated alteration of the glutathione-S-transferase activity accompanied by changes in platinum-DNA adduct formation and in epidermal growth factor receptor expression could account for the potentiation of CDDP cytotoxicity in ovarian cancer cells. Retinoids not only represent promising drugs for single-agent anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 74%
“…It is possible that DNA platination levels could be elevated as a consequence of hormone treatment, as suggested by reports that active promoter sites are preferentially platinated by the drug (42,43). We have investigated the bound-platinum levels on genomic DNA in cells treated with steroid hormones by platinum atomic absorption spectroscopy.…”
Section: Effects Of Hormones On Cell Proliferation and Sensitivity Tomentioning
confidence: 99%
“…Recent studies have shown that ATRA enhances the cytotoxicity of chemotherapeutic agents. For instance, ATRA has been shown to increase the in vitro sensitivity to cisplatin in squamous head and neck cancer and in ovarian cancer cells (Sacks et al, 1995;Aebi et al, 1997;Caliaro et al, 1997). Formelli et al have demonstrated in an in vivo model that the synthetic retinoid fenretinide enhanced activity of cisplatin and increased survival of nude mice bearing ovarian carcinoma xenografts (Formelli and Cleris, 1993).…”
mentioning
confidence: 99%